2016
DOI: 10.1017/s1368980016002482
|View full text |Cite
|
Sign up to set email alerts
|

The effect on drink sales of removal of unhealthy drinks from display in a self-service café

Abstract: Objective: The present study assessed the impact of the retailer-led removal of unhealthy beverages from display at a self-service café within a major health service. While unhealthy beverages remained available from behind the counter upon request, this was not communicated directly to customers. Design: Drinks were categorised based on the state government nutrient profiling system, classifying drinks as 'green' (best choices), 'amber' (choose carefully) and 'red' (limit). Total drink sales (as number of ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…These approaches require lower levels of personal responsibility or ‘agency’ from individuals to change their behaviour and aim to create environments that readily enable healthier choices [ 8 ]. Examples of these approaches include: applying specific taxes or levies to SSB products [ 9 , 10 ]; removing or restricting access to SSBs in institutional settings such as schools [ 11 , 12 ]; and changing serving size and placement of SSBs in other settings such as hospitals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches require lower levels of personal responsibility or ‘agency’ from individuals to change their behaviour and aim to create environments that readily enable healthier choices [ 8 ]. Examples of these approaches include: applying specific taxes or levies to SSB products [ 9 , 10 ]; removing or restricting access to SSBs in institutional settings such as schools [ 11 , 12 ]; and changing serving size and placement of SSBs in other settings such as hospitals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of our study is the cross-sectional design which means we cannot determine cause and effect relationships between purchasing location and behaviour (that is, does location drive purchasing or does desire to consume drive choice of purchase location?). However, empirical studies have shown that SSB purchases can be influenced by store-level environmental factors such as product placement [79] and pricing [80], suggesting that these factors should be considered in further research and in public health interventions.…”
Section: Discussionmentioning
confidence: 99%
“…After six weeks, the intervention reduced the proportion of ‘red’ drinks sold from 33% to 10% of total drinks sold, with a concomitant significant increase in healthier ‘amber’ and ‘green’ traffic light-classified drinks. Overall sales volume was unchanged and the retailer chose to continue with the strategy after the trial period [ 39 ]. Additionally, there is evidence that consumers of hospital food and drinks outlets would prefer the provision of healthier food items, based on a survey with a focus on vending machines of people attending a hospital in regional NSW [ 40 ].…”
Section: Discussionmentioning
confidence: 99%